AODTU-010 Ileal inflammation at the resection margin is associated with an increased risk of recurrence of post-operative ileal crohn's disease over a 10-year follow up. (17th June 2017) - Hay, I; Lynch, L; Saffouri, E; Watts, D
Abstract : Introduction: Crohn's disease recurrence following ileocolonic resection is a well-recognised clinical complication of surgical management. Studies report conflicting data regarding the preventive efficacy of immunomodulatory therapy, and there is no accepted standard of postoperative treatment. Identifying risk factors for postoperative disease recurrence may allow an opportunity to treat high-risk patients effectively. Ileal inflammation at the surgical resection margin may be such a risk factor for disease recurrence but there is little published data to support this. Method: We undertook a retrospective review of ileal marginal histology for all ileocolonic resections for Crohns disease in Forth Valley from 2005 – 2012. The data was correlated to radiological and endoscopic outcomes. Chi-squared statistical analysis was undertaken across the groups with no marginal disease against those with evidence of ileal marginal disease activity. Results: 69 patients were seen to have no evidence of ileal marginal disease at resection. Of these, 23 developed recurrent ileal disease over 10 year follow up. This contrasts with a significantly higher rate of relapse in those with ileal inflammtory disease at the resection margin, in whom 18/27 patients developed post-operative disease recurrence (p=0.003). Conclusion: This study confirms that the rate of postoperative disease recurrence is higher in those patients with inflammatory disease activity at the ileal resection margin at index surgery (follow up 3–10 years). There is a significant difference in relapse rates between the two groups, where disease recurrence is defined by evidence of inflammation at either postoperative MRE or colonoscopy, or both. Validation by larger studies is required but may allow the identification of a new cohort of Crohn's patients with a higher risk of post-operative disease relapse in whom targeted immunomodulatory therapy might be justified. Disclosure of Interest: None Declared